Molecular Switching in Confined Spaces: Effects of Encapsulating the DHA/VHF Photo‐Switch in Cucurbiturils. Issue 67 (18th September 2017) - Petersen, Michael Å.; Rasmussen, Brian; Andersen, Nicolaj N.; Sauer, Stephan P. A.; Nielsen, Mogens Brøndsted; Beeren, Sophie R.; Pittelkow, Michael
Abstract: Confinement of reactive chemical species uniquely affects chemical reactivity by restricting the physical space available and by restricting access to interactions with the solvent. In Nature, for example, confined protein binding pockets govern processes following photoisomerization reactions and the isomerizations themselves. Here we describe the first example of a dihydroazulene/vinylheptafulvene (DHA/VHF) photo‐switch functioning in water, and we show how its switching behavior is strongly influenced by supramolecular interactions with a series of cucurbit[ n ]uril (CB) host molecules. In CB7 inclusion complexes, the kinetics of the thermal VHF‐to‐DHA back‐reaction is accelerated, while in CB8 inclusion complexes, the kinetics is slowed down as compared to the free photo‐switch. The effect of the CB encapsulation of the photo‐switch can be effectively canceled by introducing a guest that binds the CB more strongly. According to DFT calculations, a stabilization of the reactive s‐ cis VHF conformer relative to the s‐ trans VHF appears to be a contributing factor responsible for the accelerated back‐reaction when encapsulated in CB7. Abstract : Switches in water : The dihydroazulene/vinylheptafulvene (DHA/VHF) photo‐switching behavior in water is strongly influenced by supramolecular interactions with a series of cucurbit[ n ]uril (CB) host molecules. In CB7 inclusion complexes, the kinetics of the thermal VHF‐to‐DHA back‐reaction is accelerated, while in CB8 inclusion complexes, the kinetics is slowed down as compared to the free photo‐switch.